Analysis of the background electrocorticogram of rats under the long-term action of hydrocarbonate load - Бурцева, Д. О.; Лукашов, С. М.; Заєць, Н. С.; Ляшенко, В. П.; Крупка, А. В. (The Journal of V.N.Karazin Kharkiv National University. Series «Biology», 1970)
There has been studied the influence of hydrocarbonate load on the electrical activity of the cerebral cortex of rats. It was found that in rats treated by NaHCO3 for 22 weeks of the experiment, there were observed the processes of desynchronization of electrical oscillations due to increasing absolute and normalized power of waves of alpha- and beta-bands. Intensity of the desynchronization depended on the period of the experiment. Changes in the electrical activity of the cerebral cortex of rats under the influence of hydrocarbonate load carried phase character and, perhaps, showed the formation of a new homeostatic state and compensatory-adaptive stress responses.